Problematika pelaksanaan pembelajaran BIPA secara daring di Inalco, Paris - Dirga, Ryan Nuansa (2021)
This qualitative research aims to describe the problems that occur during the teaching and learning process of Indonesian as Foreign Language (Bahasa Indonesia bagi Penutur Asing, BIPA) in INALCO, Paris. The data is collected by using observation and interview with the teachers and students. The result shows that both, teachers and students, prefer classroom learning. Therefore, some problems which appear in the learning process are teachers' difficulty to control students, to give feedback and there is little interaction between teachers and students.